Children's errors in mathematics understanding common misconceptions in primary schools - Hansen, Alison (Exeter, U.K. Learning Matters, 2011)
An essential reference guide to children's common errors and misconceptions in mathematics enabling trainee teachers to plan for and address errors arising in mathematics teaching.
How children learn mathematics / Alice Hansen -- Children?s mathematical errors and misconceptions : perspectives on the teacher?s role / Doreen Drews -- Number / Fiona Lawton -- Shape and space / Alice Hansen -- Measures / John Dudgeon -- Handling data / Liz Surtees -- Appendix : curriculum objectives.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain